Reconsidering Nutritional Support in Critically Ill Patients - Korwin, Amy; Honiden, Shyoko (Seminars in Respiratory and Critical Care Medicine, 2019)
Provision of nutrition is universally considered a key element of supportive care in the intensive care unit (ICU). Despite this, there is a relative dearth of high-quality data, and where available, results are often conflicting. As we understand more about the process of recovery for critically ill patients, ICU nutrition might be better thought of as active therapy that can and should be tailored to the needs of patients in more dynamic ways. With the advent of the programmable feeding pump, continuous feeding modes have become the default manner in which patients are fed in many ICUs. In the modern ICU era, where the goal of critical care has shifted from mere survival to surviving and living well, non-continuous modes of feeding may have advantages related to fewer feeding interruptions, ICU mobilization, optimizing protein synthesis and autophagy, as well as restoring gastrointestinal physiology and the circadian rhythm. More research is desperately required to provide a framework in order to guide best nutrition practices for clinicians at the bedside.
Keywords: enteral nutrition; critical illness; intensive care unit